Protective glaze, preparation method thereof and ceramic tile

By adding nano cuprous oxide solution, calcined zinc oxide and copper tailings slag to the tiles glaze, combined with vapor phase silica dispersed wrapping technology, the problem of reducing the antiviral effect of existing antiviral tiles at high temperatures is solved, and the tiles are realized Achieve the expected antiviral performance in practical applications.

CN119285226AActive Publication Date: 2025-01-10FOSHAN DONGPENG CERAMIC +3
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202410273483.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-11
Publication Date
2025-01-10
Estimated Expiration
2044-03-11

AI Technical Summary

Technical Problem

The existing antiviral tiles have poor antiviral effects, and the antiviral materials are prone to corrosion during high-temperature sintering, making it difficult for ceramic tiles to achieve the expected antiviral effect in actual applications.

Method used

A protective glaze, including basic glaze, nanocubous copper oxide solution, calcined zinc oxide and copper tailings slag, is used to disperse the nanocubous copper oxide by vapor phase silica, and combine it with copper tailings slag to stabilize its antiviral properties at high temperatures. , form excellent antiviral materials.

Benefits of technology

It significantly improves the antiviral effect of the glaze, so that the ceramic tiles still have excellent antiviral performance after high temperature firing, and can effectively fight EV71 and H3N2 viruses, achieving 97.30%-99.02% and 98.72%-99.78% antiviral activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses protective glaze, a preparation method thereof and a ceramic tile, and relates to the technical field of ceramic tiles. The protective glaze comprises the following components in parts by mass: 100 parts of basic glaze, 1-8 parts of a nano cuprous oxide solution, 0.5-4 parts of calcined zinc oxide and 0.5-3 parts of copper tailing slag, the nano cuprous oxide solution comprises nano cuprous oxide and fumed silica; the copper grade of the copper tailing slag is 0.15 to 0.25 percent. According to the protective glaze disclosed by the invention, the antiviral effect of the glaze can be remarkably improved, the protective glaze still has an excellent antiviral effect after being sintered at a high temperature, and the problem that the existing antiviral glaze is difficult to achieve an expected antiviral effect is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic tiles, and in particular to a protective glaze and a preparation method thereof, and ceramic tiles. Background Art

[0002] As people's living standards continue to improve, people pay more and more attention to the pursuit of healthy life, and the demand for antiviral is getting stronger and stronger. Therefore, tiles with antiviral function are extremely practical, but there is still a lack of tiles with antiviral function on the market.

[0003] At present, most of the ceramic tiles on the market achieve antiviral effects by coating a layer of antiviral glaze on the surface of the brick blank. The antiviral effect is achieved by adding metal zinc ions, silver oxide and other raw materials with antibacterial and antiviral effects to the antiviral glaze. However, the antiviral effect of existing antiviral glazes is poor. In addition, since high-temperature sintering is required during the preparation of ceramic tiles, the original silicate system of the glaze will corrode antiviral materials such as metal zinc ions at high temperatures, resulting in a reduction in the antiviral effect of the prepared ceramic tiles, making it difficult for the prepared ceramic tiles to achieve the expected antiviral effect in actual applications. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to propose a protective glaze that can significantly improve the antiviral effect of the glaze, and the protective glaze still has excellent antiviral effect after high-temperature firing, thereby solving the problem that existing antiviral glazes are difficult to achieve the expected antiviral effect.

[0005] Another object of the present invention is to provide a method for preparing a protective glaze, which is used to prepare the above-mentioned protective glaze and can produce a protective glaze with good antiviral effect.

[0006] Another object of the present invention is to propose a ceramic tile, comprising a brick layer and a protective glaze layer located on the surface of the brick layer, wherein the protective glaze layer is fired by the above-mentioned protective glaze, so that the ceramic tile has better antiviral performance and can achieve the expected antiviral effect in practical applications.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] A protective glaze comprises the following components in parts by weight: 100 parts of basic glaze, 1 to 8 parts of nano cuprous oxide solution, 0.5 to 4 parts of calcined zinc oxide and 0.5 to 3 parts of copper tailings;

[0009] The nano cuprous oxide solution comprises nano cuprous oxide and fumed silicon dioxide;

[0010] The copper grade of the copper tailings is 0.15-0.25%.

[0011] Preferably, calculated by mass percentage, the solid content of the nano cuprous oxide solution is 40% to 60%;

[0012] In the nano cuprous oxide solution, the viscosity of the fumed silica is ≤30CP.

[0013] Preferably, the copper grade of the copper tailings is 0.18-0.22%.

[0014] Preferably, the particle size of the nano cuprous oxide is 100-800 nm.

[0015] Preferably, calculated by mass, the protective glaze further includes 0.3 to 1.5 parts of aluminum oxide.

[0016] Preferably, calculated by weight, the protective glaze further includes 0.05 to 0.3 parts of zirconium silicate.

[0017] Preferably, the protective glaze comprises the following components in parts by mass: 100 parts of basic glaze, 4 parts of nano cuprous oxide solution, 2 parts of calcined zinc oxide and 1 part of copper tailings.

[0018] A method for preparing a protective glaze, used for preparing the above-mentioned protective glaze, comprises the following steps: according to a proportion, adding a nano cuprous oxide solution, calcined zinc oxide and copper tailings to a basic glaze, then adding sodium hexametaphosphate and sodium tripolyphosphate, performing degumming and ball milling, adding a liquid degumming agent in the middle of the ball milling for degumming, and obtaining the protective glaze after the ball milling is completed.

[0019] A ceramic tile comprises a brick layer and a protective glaze layer located on the surface of the brick layer, wherein the protective glaze layer is formed by firing the protective glaze.

[0020] The technical solution provided in the embodiment of the present application may include the following beneficial effects: the technical solution can effectively inhibit the oxidation of nano-cuprous oxide at high temperature by first using fumed silica to disperse and wrap nano-cuprous oxide, and then adding copper tailings slag to the glaze, so that the nano-cuprous oxide can still form an excellent antiviral material with zinc oxide after high-temperature sintering, and exert an excellent antiviral effect. The antiviral effect of the protective glaze obtained is good, and the expected antiviral effect can be achieved in practical applications. DETAILED DESCRIPTION

[0021] In order to facilitate the understanding of the present invention, the present invention is described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0022] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. Raw materials used without specifying the manufacturer are all conventional products that can be obtained through commercial purchase.

[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0024] The technical solution of the present invention is further explained below in conjunction with specific implementation methods.

[0025] A protective glaze comprises the following components in parts by weight: 100 parts of basic glaze, 1 to 8 parts of nano cuprous oxide solution, 0.5 to 4 parts of calcined zinc oxide and 0.5 to 3 parts of copper tailings;

[0026] The nano cuprous oxide solution comprises nano cuprous oxide and fumed silicon dioxide;

[0027] The copper grade of the copper tailings is 0.15-0.25%.

[0028] It is worth noting that the technical solution can significantly enhance the antiviral effect of the glaze by adding nano cuprous oxide solution, calcined zinc oxide and copper tailings to the base glaze through the synergistic effect of the three. Moreover, the protective glaze still has excellent antiviral effect after high-temperature firing, with the antiviral activity against EV71 virus reaching 97.30% to 99.02%, and the antiviral activity against H3N2 virus reaching 98.72% to 99.78%.

[0029] Further explanation, the antiviral ability of nano cuprous oxide is stronger than zinc oxide at low temperature, but nano cuprous oxide is easily oxidized at high temperature, which makes its antiviral ability drop sharply. Therefore, the technical solution disperses nano cuprous oxide using fumed silica in advance, so that nano cuprous oxide is dispersed and wrapped by fumed silica, and a nano cuprous oxide solution is obtained. By using fumed silica for wrapping, nano cuprous oxide (Cu2O) at high temperature can be stabilized, and nano cuprous oxide is reduced to be oxidized at high temperature. If fumed silica is not used in advance to disperse and wrap nano cuprous oxide, nano cuprous oxide is easily oxidized and corroded by other components in the glaze at high temperature and loses its antiviral effect. At the same time, the technical solution also adds copper tailings to the protective glaze, and the copper tailings are conducive to causing the effect of rich copper elements in the glaze system, which can further stabilize the nano cuprous oxide at high temperature, so that nano cuprous oxide is not easily oxidized and reduced when fired at high temperature. Therefore, the technical solution can effectively inhibit the oxidation of nano-cuprous oxide at high temperature by first using fumed silica to disperse and encapsulate nano-cuprous oxide, and by adding copper tailings slag to the glaze, so that the nano-cuprous oxide can still form an excellent antiviral material with zinc oxide after high-temperature sintering, and exert an excellent antiviral effect.

[0030] Specifically, the protective glaze of the present technical solution includes the following components by mass: 100 parts of basic glaze, 1 to 8 parts of nano cuprous oxide solution, 0.5 to 4 parts of calcined zinc oxide and 0.5 to 3 parts of copper tailings; calculated by the dry weight of the basic glaze, 1 to 8 parts of nano cuprous oxide solution, 0.5 to 4 parts of calcined zinc oxide and 0.5 to 3 parts of copper tailings are added to 100 parts of the basic glaze. Under this ratio, the ceramic tile can obtain excellent antiviral performance. If the amount of nano cuprous oxide solution, calcined zinc oxide and copper tailings is too small, the antiviral performance will be significantly reduced; if the amount of nano cuprous oxide solution, calcined zinc oxide and copper tailings is too high, it will not only increase the cost, but also cuprous oxide will bring in color, making the protective glaze too dark, which will affect the appearance of the product. At the same time, too much metal oxide (cuprous oxide and zinc oxide) will easily cause surface defects on the glaze, such as caves, pinholes and other surface defects.

[0031] It is worth mentioning that copper tailings with a copper grade of 0.15% to 0.25% are beneficial to creating a copper-rich effect in the glaze system, which can stabilize nano-cuprous oxide at high temperatures and make nano-cuprous oxide less likely to be oxidized and reduced, thereby improving the antiviral stability of the protective glaze, so that the protective glaze still has excellent antiviral effect after high-temperature firing (1100-1200°C).

[0032] Specifically, the copper content in copper ore is called grade, which is usually expressed as a percentage, that is, the weight of copper contained in a unit weight of ore accounts for the percentage of the total weight. The copper grade of copper tailings in this technical solution is 0.15% to 0.25%, which means that the copper content in the unit weight of copper tailings is 0.15% to 0.25%.

[0033] Specifically, copper tailings are powdery or fine granular waste residues left after copper ore is crushed and selected. The basic glaze used in the technical solution is a protective glaze commonly used in the field of ceramic tiles.

[0034] Further explanation, calculated by mass percentage, the solid content of the nano cuprous oxide solution is 40% to 60%;

[0035] In the nano cuprous oxide solution, the viscosity of the fumed silica is ≤30CP.

[0036] It is worth noting that this technical solution controls the solid content of the nano cuprous oxide solution to 40% to 60%, and controls the viscosity of the fumed silica to below 30CP. Under this condition, the fumed silica can provide enough silica to encapsulate the nano cuprous oxide, and at the same time will not significantly increase the viscosity of the glaze, thereby affecting the basic performance of the glaze slurry to flow freely. If the solid content is too low, the encapsulation effect will be weakened, and it is easy to cause the nano cuprous oxide to oxidize at high temperature, affecting the antiviral effect; if the solid content is too high, the viscosity will increase, which will affect the later performance of the glaze slurry, resulting in defects on the surface of the obtained tiles and unable to be produced normally.

[0037] Preferably, in a preferred embodiment of the present invention, the solid content of the nano cuprous oxide solution is 45% to 55%, so that the antiviral effect of the prepared protective glaze is better.

[0038] Further explanation: the copper grade of the copper tailings is 0.18-0.22%.

[0039] It is worth noting that copper tailings with a copper grade of about 0.18-0.22% are beneficial to creating a copper-rich effect in the glaze system, and can stabilize nano-cuprous oxide at high temperatures, making it less likely to be oxidized and reduced.

[0040] Preferably, in a most optimal embodiment of the present invention, copper tailings with a copper grade of 0.2% are selected.

[0041] Further description, the particle size of the nano cuprous oxide is 100-800 nm.

[0042] It is worth noting that the use of nano cuprous oxide with a particle size of 100 to 800 nm in the protective glaze can achieve better antibacterial and antiviral effects. If the particle size of nano cuprous oxide is less than 100 nm, the particle size of nano cuprous oxide is too small, which is easy to agglomerate and affect the dispersion effect, resulting in a decrease in antiviral performance. At the same time, the smaller the size, the higher the cost, which is not suitable for industrial production; if the particle size of nano cuprous oxide is greater than 800 nm, the specific surface area of ​​nano cuprous oxide particles is too small, and the contact surface with bacteria and viruses is reduced, which will affect the subsequent antibacterial and antiviral effects, resulting in a decrease in the antiviral effect.

[0043] Further description, calculated by weight, the protective glaze also includes 0.3 to 1.5 parts of aluminum oxide.

[0044] Since the firing temperature of the composite antiviral agent composed of nano cuprous oxide solution, calcined zinc oxide and copper tailings is relatively low, the technical solution adds an additional 0.3 to 1.5 parts of aluminum oxide to the protective glaze. Aluminum oxide can balance the firing temperature reduced by the composite antiviral agent, so that the firing temperature of the protective glaze matches the firing temperature of the brick.

[0045] As a further explanation, the protective glaze further comprises 0.05 to 0.3 parts of zirconium silicate, calculated by weight.

[0046] It should be noted that since nano cuprous oxide is light green at high temperatures, it will affect the appearance of the glaze. Therefore, the technical solution adds 0.05 to 0.3 parts of zirconium silicate to the protective glaze. The zirconium silicate and calcined zinc oxide work together to slightly emulsify and reduce the light green color of the cuprous oxide, making the color of the protective glaze suitable for use with tiles.

[0047] Further explanation, the protective glaze includes the following components in parts by mass: 100 parts of basic glaze, 4 parts of nano cuprous oxide solution, 2 parts of calcined zinc oxide and 1 part of copper tailings.

[0048] In a preferred embodiment of the present invention, the protective glaze includes 100 parts of basic glaze, 4 parts of nano cuprous oxide solution, 2 parts of calcined zinc oxide and 1 part of copper tailings. The ceramic tiles made of the protective glaze have an antiviral activity of 98.65% against EV71 virus and 99% against H3N2 virus, and the glaze surface effect is good and basically free of defects.

[0049] A method for preparing a protective glaze, used for preparing the above-mentioned protective glaze, comprises the following steps: according to a proportion, adding a nano cuprous oxide solution, calcined zinc oxide and copper tailings to a basic glaze, then adding sodium hexametaphosphate and sodium tripolyphosphate, performing degumming and ball milling, adding a liquid degumming agent in the middle of the ball milling for degumming, and obtaining the protective glaze after the ball milling is completed.

[0050] Specifically, in one embodiment of the present invention, the preparation method of the protective glaze includes the following steps: according to the proportion, 1-8 parts of nano cuprous oxide solution, 0.5-4 parts of calcined zinc oxide and 0.5-3 parts of copper tailings are first added to 100 parts of the basic glaze, and then 0.15-0.4 parts of sodium hexametaphosphate and 0.08-0.3 parts of sodium tripolyphosphate are added to perform debonding and ball milling, and 0.05-0.3 parts of liquid debonding agent (such as PC67) is added in the middle of ball milling (about 1 hour before the ball milling) for debonding, and the protective glaze is obtained after the ball milling is completed.

[0051] A ceramic tile comprises a brick layer and a protective glaze layer located on the surface of the brick layer, wherein the protective glaze layer is formed by firing the protective glaze.

[0052] By coating the above-mentioned protective glaze on the surface of the brick blank, ceramic tiles with excellent antiviral effect can be produced after firing, and the produced ceramic tiles can achieve the expected antiviral effect in practical applications.

[0053] Example 1

[0054] The protective glaze of this embodiment includes the following components by weight: 100 parts of basic glaze, 2 parts of nano cuprous oxide solution, 2 parts of calcined zinc oxide, 1 part of copper tailings, 1 part of aluminum oxide and 0.15 parts of zirconium silicate; wherein the copper grade of the copper tailings is 0.2%, and the particle size of the nano cuprous oxide is 100-800 nm;

[0055] The nano cuprous oxide solution is composed of nano cuprous oxide and fumed silicon dioxide; the solid content of the nano cuprous oxide solution is 50%, and the viscosity of the fumed silicon dioxide in the nano cuprous oxide solution is 28CP;

[0056] The preparation method of the protective glaze of this embodiment is as follows: according to the proportion, first add nano cuprous oxide solution, calcined zinc oxide, copper tailings, aluminum oxide and zirconium silicate to the basic glaze, then add 0.2 parts of sodium hexametaphosphate and 0.1 parts of sodium tripolyphosphate, and perform debonding and ball milling. In the middle of the ball milling (about 1 hour before the ball milling), add 0.15 parts of liquid debonding agent (PC67) for debonding, and obtain the protective glaze after the ball milling is completed.

[0057] Example 2

[0058] The protective glaze of this embodiment includes the following components by weight: 100 parts of basic glaze, 3 parts of nano cuprous oxide solution, 3 parts of calcined zinc oxide, 1.5 parts of copper tailings, 0.9 parts of aluminum oxide and 0.2 parts of zirconium silicate; wherein the copper grade of the copper tailings is 0.22%, and the particle size distribution of the nano cuprous oxide is 100-800 nm;

[0059] The nano cuprous oxide solution is composed of nano cuprous oxide and fumed silica; the solid content of the nano cuprous oxide solution is 55%, and the viscosity of the fumed silica in the nano cuprous oxide solution is 30CP;

[0060] The preparation method of the protective glaze of this embodiment is as follows: according to the proportion, first add nano cuprous oxide solution, calcined zinc oxide, copper tailings, aluminum oxide and zirconium silicate to the basic glaze, then add 0.2 parts of sodium hexametaphosphate and 0.1 parts of sodium tripolyphosphate, and perform debonding and ball milling. In the middle of the ball milling (about 1 hour before the ball milling), add 0.15 parts of liquid debonding agent (PC67) for debonding, and obtain the protective glaze after the ball milling is completed.

[0061] Example 3

[0062] The protective glaze of this embodiment includes the following components by weight: 100 parts of basic glaze, 4 parts of nano cuprous oxide solution, 4 parts of calcined zinc oxide, 3 parts of copper tailings, 0.3 parts of aluminum oxide and 0.05 parts of zirconium silicate; wherein the copper grade of the copper tailings is 0.2%, and the particle size of the nano cuprous oxide is 100-800 nm;

[0063] The nano cuprous oxide solution is composed of nano cuprous oxide and fumed silicon dioxide; the solid content of the nano cuprous oxide solution is 50%, and the viscosity of the fumed silicon dioxide in the nano cuprous oxide solution is 28CP;

[0064] The preparation method of the protective glaze of this embodiment is as follows: according to the proportion, first add nano cuprous oxide solution, calcined zinc oxide, copper tailings, aluminum oxide and zirconium silicate to the basic glaze, then add 0.2 parts of sodium hexametaphosphate and 0.1 parts of sodium tripolyphosphate, and perform debonding and ball milling. In the middle of the ball milling (about 1 hour before the ball milling), add 0.15 parts of liquid debonding agent (PC67) for debonding, and obtain the protective glaze after the ball milling is completed.

[0065] Example 4

[0066] The protective glaze of this embodiment includes the following components by mass: 100 parts of basic glaze, 6 parts of nano cuprous oxide solution, 1 part of calcined zinc oxide, 2 parts of copper tailings, 1 part of aluminum oxide and 0.1 part of zirconium silicate; wherein the copper grade of the copper tailings is 0.2%, and the particle size of the nano cuprous oxide is 100-800 nm;

[0067] The nano cuprous oxide solution is composed of nano cuprous oxide and fumed silicon dioxide; the solid content of the nano cuprous oxide solution is 50%, and the viscosity of the fumed silicon dioxide in the nano cuprous oxide solution is 28CP;

[0068] The preparation method of the protective glaze of this embodiment is as follows: according to the proportion, first add nano cuprous oxide solution, calcined zinc oxide, copper tailings, aluminum oxide and zirconium silicate to the basic glaze, then add 0.3 parts of sodium hexametaphosphate and 0.08 parts of sodium tripolyphosphate, and perform debonding and ball milling. In the middle of the ball milling (about 1 hour before the ball milling), add 0.2 parts of liquid debonding agent (PC67) for debonding, and obtain the protective glaze after the ball milling is completed.

[0069] Example 5

[0070] The protective glaze of this embodiment includes the following components by weight: 100 parts of basic glaze, 8 parts of nano cuprous oxide solution, 0.5 parts of calcined zinc oxide, 0.5 parts of copper tailings, 1.5 parts of aluminum oxide and 0.3 parts of zirconium silicate; wherein the copper grade of the copper tailings is 0.18%, and the particle size of the nano cuprous oxide is 100-800 nm;

[0071] The nano cuprous oxide solution is composed of nano cuprous oxide and fumed silicon dioxide; the solid content of the nano cuprous oxide solution is 50%, and the viscosity of the fumed silicon dioxide in the nano cuprous oxide solution is 28CP;

[0072] The preparation method of the protective glaze of this embodiment is as follows: according to the proportion, nano cuprous oxide solution, calcined zinc oxide, copper tailings, aluminum oxide and zirconium silicate are first added to the basic glaze, and then 0.15 parts of sodium hexametaphosphate and 0.3 parts of sodium tripolyphosphate are added, and debonding and ball milling are carried out. In the middle of the ball milling (about 1 hour before the ball milling), 0.25 parts of liquid debonding agent (PC67) are added for debonding, and the protective glaze is obtained after the ball milling is completed.

[0073] Specifically, the protective glaze prepared in Examples 1-5 is used to prepare ceramic tiles. The preparation method is as follows: the protective glaze prepared in Examples 1-5 is coated on the surface of different bricks to prepare ceramic tiles respectively. The antiviral properties of the ceramic tiles prepared using the protective glaze in Examples 1-5 are tested respectively. The test results are shown in Table 1 below.

[0074] Table 1 Antiviral performance test results of Examples 1-5

[0075]

[0076] It can be seen from the antiviral performance test results in Table 1 that the tiles prepared in Examples 1-5 all have excellent antiviral activity, with the antiviral activity against EV71 virus reaching 97.30% to 99.02%, and the antiviral activity against H3N2 virus reaching 98.72% to 99.78%.

[0077] Comparative Examples 1-3

[0078] The proportions of the raw materials in the protective glazes of Comparative Examples 1-3 are shown in Table 2 below:

[0079] Table 2 Ratios of raw materials in the protective glazes of comparative examples 1-3

[0080] Comparative Example 1 Comparative Example 2 Comparative Example 3 Basic glaze 100 copies 100 copies 100 copies Nano cuprous oxide solution 0.3 parts 4 servings 4 servings Calcined zinc oxide 0.3 parts 0 2 servings Copper tailings 0.3 parts 0 0 Alumina 1 serving 1 serving 1 serving Zirconium silicate 0.15 0.15 0.15

[0081] Among them, the copper grade of the copper tailings used in Comparative Example 1 is 0.2%; the particle size of the nano cuprous oxide used in Comparative Examples 1-3 is 100-800nm, the solid content of the nano cuprous oxide solution is 50%, and the viscosity of the fumed silica in the nano cuprous oxide solution is 28CP; the preparation method of the protective glaze of Comparative Examples 1-3 is the same as that of Example 1, and the protective glazes are prepared respectively according to the preparation method of Example 1.

[0082] The protective glazes of Comparative Examples 1-3 were used to prepare ceramic tiles. The preparation method was as follows: the protective glazes of Comparative Examples 1-3 were coated on the surfaces of different brick blanks to prepare ceramic tiles respectively. The antiviral properties of the ceramic tiles prepared using the protective glazes of Comparative Examples 1-3 were tested respectively. The test results are shown in Table 3 below.

[0083] Table 3 Antiviral performance test results of Comparative Examples 1-3

[0084]

[0085] It can be seen from Table 3 that in Comparative Example 1, when only 0.3 parts of nano cuprous oxide solution, 0.3 parts of calcined zinc oxide and 0.3 parts of copper tailings were added to the protective glaze, the antiviral performance of the tiles made using the protective glaze was significantly reduced, with the antiviral activity against EV71 virus being only 26.52% and the antiviral activity against H3N2 virus being only 35.41%.

[0086] From the antiviral test results of Comparative Example 2, it can be seen that if only 4 parts of nano cuprous oxide solution are added to the protective glaze without adding calcined zinc oxide and copper tailings, the antiviral performance of the resulting tiles will be significantly reduced, with the antiviral activity against EV71 virus being only 55.26% and the antiviral activity against H3N2 virus being only 60.38%.

[0087] From the antiviral test results of Comparative Example 3, it can be seen that if only 4 parts of nano cuprous oxide solution and 2 parts of calcined zinc oxide are added to the protective glaze without adding copper tailings, the antiviral performance of the protective glaze will also decrease. The tiles made of this protective glaze have an antiviral activity of 71.53% against EV71 virus and 81.71% against H3N2 virus.

[0088] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.

Claims

1. A protective glaze, characterized in that: The invention comprises the following components in parts by weight: 100 parts of basic glaze, 1 to 8 parts of nano cuprous oxide solution, 0.5 to 4 parts of calcined zinc oxide and 0.5 to 3 parts of copper tailings; The nano cuprous oxide solution comprises nano cuprous oxide and fumed silicon dioxide; The copper grade of the copper tailings is 0.15-0.25%.

2. The protective glaze according to claim 1, characterized in that: Calculated by mass percentage, the solid content of the nano cuprous oxide solution is 40% to 60%; In the nano cuprous oxide solution, the viscosity of the fumed silica is ≤30CP.

3. The protective glaze according to claim 1, characterized in that: The copper grade of the copper tailings is 0.18-0.22%.

4. The protective glaze according to claim 1, characterized in that: The particle size of the nano cuprous oxide is 100-800nm.

5. The protective glaze according to claim 1, characterized in that: Calculated by weight, the protective glaze also includes 0.3 to 1.5 parts of aluminum oxide.

6. The protective glaze according to claim 5, characterized in that: Calculated by weight, the protective glaze also includes 0.05 to 0.3 parts of zirconium silicate.

7. The protective glaze according to claim 1, characterized in that: The protective glaze comprises the following components in parts by mass: 100 parts of basic glaze, 4 parts of nano cuprous oxide solution, 2 parts of calcined zinc oxide and 1 part of copper tailings.

8. A method for preparing a protective glaze, characterized in that: The method for preparing the protective glaze according to any one of claims 1 to 7 comprises the following steps: adding nano cuprous oxide solution, calcined zinc oxide and copper tailings to a basic glaze according to a proportion, then adding sodium hexametaphosphate and sodium tripolyphosphate, performing degumming and ball milling, adding a liquid degumming agent in the middle of the ball milling for degumming, and obtaining the protective glaze after the ball milling is completed.

9. A ceramic tile, characterized in that: It comprises a brick layer and a protective glaze layer located on the surface of the brick layer, and the protective glaze layer is fired by the protective glaze according to any one of claims 1-7.

Citation Information

Patent Citations

  • AES (acrylonitrile-ethylene propylene diene monomer rubber-styrene) composite material and preparation method thereof

    CN108395659A

  • AES composite material

    CN109627661A

  • Antiviral coating and preparation method thereof

    CN111849266A

  • Paint system with anti-fouling property

    CN113354972A

  • Nano cuprous oxide antibacterial mildew-proof master batch and preparation method thereof, plastic product and preparation method thereof

    CN113881135A